Analysis of the Performance of Aerial Work Platform Working Device Based on Virtual Prototype and Finite Element Method. (December 2016) - Guo, Jinquan; He, Hongwen; Sun, Chao
Abstract: In this paper, a model of aerial work platform working device based on virtual prototype and finite element method was established. Through the software ADAMS kinematic simulation, we got the moving velocity and acceleration. The moving velocity and acceleration showed that the aerial work platform working device met the standards of the national safety standard. Through the dynamics simulation, we got the joints force between working device, we input the joints force into the finite element model established by the software of Hyperworks. The simulation result of working device stress distribution showed that the chose material met the working requirements; the structural design of working device was reasonable.